2023
DOI: 10.1108/jtf-06-2023-0144
|View full text |Cite
|
Sign up to set email alerts
|

Future strategies for tourism destination management: post COVID-19 lessons observed from Borobudur, Indonesia

Jasper Hessel Heslinga,
Mohamad Yusuf,
Janianton Damanik
et al.

Abstract: PurposeThe purpose of this viewpoint paper is to show practical post COVID-19 observations as lessons for the future of tourism destination management and help inspire the tourism industry and academic community.Design/methodology/approachThis paper is based on observations by, and discussions among, both international and Indonesian tourism experts and relate to the case of the famous UNESCO World heritage site, the Borobudur temple, in Indonesia.FindingsAs a result, the authors observed the following measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This is caused by buying power falling in accompaniment with community economic downturn and the keenness of business competition in the community (Sari et al, 2022). Both Rindrasih (2018) and Heslinga et al (2023) in their studies have revealed that the recovery of tourism from disaster is indeed dynamic and full of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…This is caused by buying power falling in accompaniment with community economic downturn and the keenness of business competition in the community (Sari et al, 2022). Both Rindrasih (2018) and Heslinga et al (2023) in their studies have revealed that the recovery of tourism from disaster is indeed dynamic and full of challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its status, the increasing number of visitors has had major economic benefits for the community, but it has also been creating overtourism-related problems. Heslinga et al . (2024) advocate local visitor management strategies to address overtourism including setting limits on the number of visitors, increasing the visitor area, providing guided tours only, working with price mechanisms, mitigating the physical impacts of visits and involving the local community in the value chain.…”
Section: Visitor Managementmentioning
confidence: 99%